Faktor-Faktor yang Berhubungan dengan Status Gizi pada Remaja di SMP Negeri 262 Jakarta Timur Tahun 2024 - Alfiyatur Rahmah; Ony Linda; Dian Kholika Hamal (Yayasan Literasi Sains Indonesia, 2024)
Teenagers are a group that is easily influenced by external cultural influences because they are going through a period of searching for theirs identify. Nutritional status is the condition of the body as a result of the food consumed every day. The aim of this research was to determine factors related to nutritional status in students at SMP Negeri 262 East Jakarta. The type of research that will be used is quantitative research with a cross sectional design. Data collection was carried out by direct measurement with a weight scale, microtoise. The sampling technique in this research used Proportional Random Sampling with a total population of 452 students at SMP Negeri 262 Jakarta, classes VII and VIII, and the sample taken was 156 students. The analysis that will be used includes univariat analysis and bivariate analysis, while the statistical test used is the chi square test. Univariate results showed that 58,3% of teenager’s had poor nutritional status, 73,7% of teenager’s had low family income, 55,1% of teenager’s feel dissatisfied, and 62,8% of teenager’s have insufficient nutritional knowledge. The result of statistical test show that there is a significant relationship between maternal education p value (0,002) and body image p value (0,007) with nutritional status in adolescents. Meanwhile, the variable that did not have a significant relationship were the family income variables p value (1,000), physical activity p value (0,359), nutritional knowledge p value (0,117).